PENGARUH KEBIJAKAN NATIONAL SWORD CINA TERHADAP EKSPOR LIMBAH PADAT INGGRIS TAHUN 2018-2019 - Rantika, Amalia; Oktyari R., Umi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
China used to import fifty-six percent of the entire world solid waste to be used as raw material for manufacturing production. Due to the bad quality of couple kinds of waste and massive foreign waste, China launched National Sword Policy which that has been effective since January 2018. This policy impact on United Kingkom as one of the waste exporter. This research described the response’s United Kingdom to China National Sword PolicyThis qualitative research is document analysis using data from book, journals, newspapers and websites such as www.gov.uk and www.greenpeace.com to describe United Kingdom’s adjustment for its policies. Nation-state level analysis with liberalism perspectives about export and rational choice theories was used to elaborate United Kingdom’s new measures. The result showed that United Kingdom has to adjust its environmental regulatios since National Sword Policy in China bans twenty-four its  solid waste export. First, UK ban on single-use plastic items started from 2020. Second, the UK tried to get places to dump for its waste. Malaysia, Thailand, Vietnam, and Indonesia will be targeted for UK waste export alternatives. The rational choice has directed UK to take lesson from China that this similar policy should be implemented too since good waste management is a necessary currently. Investment in industries of waste management, such as recycling star growing in UKKeywords: National Sword Policy, Foreign Waste, Export, Import, Waste